160 Long-term cognitive effects of perampanel in paediatric patients with epilepsy by responder status and dose. Issue 6 (27th May 2022) - Gidal, Barry; Meador, Kimford J; Patten, Anna; Malhotra, Manoj; Ngo, Leock Y
Abstract : Background: The long-term (≤1-year) effects of adjunctive perampanel on cognition by responder status and modal dose were assessed in paediatric patients (aged 4–<12 years) with partial-onset seizures (with/without secondarily generalised seizures) or primary generalised tonic-clonic seizures during Study 311 (NCT02849626 ). Methods: Core Study (4-week pretreatment/23-week treatment) completers could enter the Extension (29-week maintenance/4-week follow-up). The Aldenkamp-Baker Neuropsychological Assessment Schedule [ABNAS] was used to assess cognition (change from baseline, Weeks 23/52) by total seizure response category (<50%/≥50%/≥75%/100% responder) and modal dose (mg/day). Results: Mean (standard deviation) change from baseline in total ABNAS for Weeks 23 and 52 by response category was: <50%, 3.7 (11.5) and -3.2 (16.8); ≥50%, -4.7 (13.8) and -3.7 (18.4); ≥75%, -2.1 (11.4) and -4.2 (14.8); 100%, -1.6 (18.3) and -0.6 (20.6), respectively; and by modal dose was: <4 mg/day, -5.8 (7.3) and -2.0 (7.2); 4 mg/day, -4.8 (22.4) and -10.4 (25.6); >4–6 mg/day, 1.3 (8.3) and -1.3 (10.2); >6–8 mg/day, -0.5 (10.7) and 1.9 (9.4); >8–12 mg/day, -0.1 (12.8) and -7.4 (20.2); >12–16 mg/day, 2.2 (12.4) and 1.1 (14.8), respectively. Conclusion: Adjunctive perampanel had few long-term effects on cognition in paediatric patients, regard- less of responder status and modal dose. Funding: Eisai Inc. 11m2anoj_malhotra@eisai.com